Recommendations for EU guidelines for the establishment of national focal points for the comprehensive integrated medical support of trafficked victims - Sörensen, Patsy (Antwerpen: Payoke; Universiteit Antwerpen, 2012)
"Payoke ; Universiteit Antwerpen ; foreword : Patsy Sörensen"